How IT Support a Telecommunication Company’s Agility to Respond Changing Market Needs? : Literature Review - Apol Pribadi; Agussalim; Seftin Fitri Ana Wati; Anita Wulansari; Anindo Saka Fitri; Eristya Maya Safitri (IJCONSIST JOURNALS, 2022)
The phenomenon of very dynamic and competitive business competition requires every telecommunication company to be adaptive in all changes. Now information technology does not only play a role in supporting business processes. IT is expected to play a major role in supporting the company's agility to adapt to the business environment. Corporate agility can provide various advantages, namely the organization is able to detect changes early and explore various solution options as a decision-making process in creating innovation. This journal provides an effective conceptual model related to how information technology is able to create organizational agility in telecommunications companies. This conceptual model is expected to be a reference for the adoption of information technology in providing a fit impact for the company.